1993
DOI: 10.1159/000247218
|View full text |Cite
|
Sign up to set email alerts
|

Topical Tiacrilast, a Potent Mast Cell Degranulation Inhibitor, Does Not Improve Adult Atopic Eczema

Abstract: Tiacrilast is a potent mast cell degranulation inhibitor in vitro and in animal studies. Since mast cells and their mediators are possibly involved in atopic eczema, we have studied a topically applied 3% hydrogel formulation of tiacrilast against vehicle in a multicenter, double-blind, placebo-controlled trial. Drug or vehicle were applied on involved skin for 28 days. Efficacy was assessed weekly using a 4-point scale for erythema, scaling, induration, exudation and pruritus. An overall assessment of the sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Accordingly, the application of mast cell degranulation inhibitors or stabilizers seems reasonable. However, in a multicenter, double‐blind, placebo‐controlled trial applying 3% hydrogel formulation of tiacrilast (mast cell inhibitor) against vehicle in atopic dermatitis, there was no significant improvement of pruritus 125 . In another study, pruritus in children with AE responded to topical sodium cromoglycate, 126 which was proven by a recent placebo‐controlled study 127 …”
mentioning
confidence: 99%
“…Accordingly, the application of mast cell degranulation inhibitors or stabilizers seems reasonable. However, in a multicenter, double‐blind, placebo‐controlled trial applying 3% hydrogel formulation of tiacrilast (mast cell inhibitor) against vehicle in atopic dermatitis, there was no significant improvement of pruritus 125 . In another study, pruritus in children with AE responded to topical sodium cromoglycate, 126 which was proven by a recent placebo‐controlled study 127 …”
mentioning
confidence: 99%
“…3,4 Clinical studies of mast cell degranulation inhibition in AD patients have produced divergent results with both improvement of the eczema seen in some, 5,6 but not all studies. Several authors describe an increased density of mast cells in AD 1,2 and speculate on the pathophysiological relevance of mast cells in AD.…”
mentioning
confidence: 99%
“…Several authors describe an increased density of mast cells in AD 1,2 and speculate on the pathophysiological relevance of mast cells in AD 3,4 . Clinical studies of mast cell degranulation inhibition in AD patients have produced divergent results with both improvement of the eczema seen in some, 5,6 but not all studies 7,8 . However, mast cell density has not been shown to correlate with severity of AD, 9 and plasma levels of mast cell mediators in AD have been found to be normal.…”
mentioning
confidence: 99%
“…Tryptase and histamine, released by mast cells, lead to the induction of pruritus in AD. Some studies have reported the usefulness of mast cell stabilizers in AD (2b, B) 121 . However, further controlled trials are needed.…”
Section: Resultsmentioning
confidence: 99%